2011
DOI: 10.1016/j.jfluidstructs.2011.04.008
|View full text |Cite
|
Sign up to set email alerts
|

Piezoelectric coupling in energy-harvesting fluttering flexible plates: linear stability analysis and conversion efficiency

Abstract: This paper investigates the energy harvested from the flutter of a plate in an axial flow by making use of piezoelectric materials. The equations for fully-coupled linear dynamics of the fluid-solid and electrical systems are derived. The continuous limit is then considered, when the characteristic length of the plate's deformations is large compared to the piezoelectric patches' length. The linear stability analysis of the coupled system is addressed from both a local and global point of view. Piezoelectric e… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

9
152
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 181 publications
(161 citation statements)
references
References 47 publications
9
152
0
Order By: Relevance
“…Recently, flow-induced vibration of flexible structures has been suggested as an alternative to overcome the drawbacks of wind-turbine-based wind energy generator including structural complexity, the large volume and weight, high cost of manufacturing and installation, low efficiency and noise. Most research in this area is focused on piezoelectric materials [4][5][6][7] such as lead zirconium titanate and polyvinylidene fluoride, where a deformation of piezoelectric material gives rise to electrical energy. The recently invented triboelectric generator harvests mechanical energy through a periodic contact motion based on the coupling of the triboelectric and electrostatic effects, and many approaches have been carried out to improve the electrical output performance of the triboelectric generator [8][9][10][11][12][13][14][15][16] .…”
mentioning
confidence: 99%
“…Recently, flow-induced vibration of flexible structures has been suggested as an alternative to overcome the drawbacks of wind-turbine-based wind energy generator including structural complexity, the large volume and weight, high cost of manufacturing and installation, low efficiency and noise. Most research in this area is focused on piezoelectric materials [4][5][6][7] such as lead zirconium titanate and polyvinylidene fluoride, where a deformation of piezoelectric material gives rise to electrical energy. The recently invented triboelectric generator harvests mechanical energy through a periodic contact motion based on the coupling of the triboelectric and electrostatic effects, and many approaches have been carried out to improve the electrical output performance of the triboelectric generator [8][9][10][11][12][13][14][15][16] .…”
mentioning
confidence: 99%
“…In recent years, Flow-Induced Vibrations like Vortex-induced Vibrations (VIV), Transverse Galloping (TG) oscillations or Flutter have been considered as a new mean to harvest energy from fluid flows (Bernitsas et al, 2008;Barrero-Gil et al, 2010Sanchez-Sanz et al, 2009;Grouthier et al, 2013;Abdelkefi et al, 2013;Doare and Michelin, 2011;Allen and Smits, 2001, to name only a few). The basic idea is to take advantage of these phenomena to convert part of the kinetic energy of the flow into oscillatory mechanical energy of the elastic body; thereafter, the mechanical energy of the body may be converted into electrical energy by electromagnetic, piezoelectric, or electrostatic means.…”
Section: Introductionmentioning
confidence: 99%
“…There are several literatures about the response of flexible piezoelectric energy harvester (FPEH) placed in a cross-flow and obtained the maximal strain energy and output power. To maximize the amount of power generated by the eel, many factors have been considered in the investigation, such as the thickness and stiffness of the eel materials, the eel length, the bluff body width and the spacing between the body and eel head [3][4]. The feasibility and performance of harvesting the electrical charge by a resistive circuit was recently studied, and it was shown that both the stability of the system and the fluttering dynamics are influenced by electrical coupling [5][6].…”
mentioning
confidence: 99%